Pengaruh Kualitas Produk dan Social Media Marketing melalui Marketplace Facebook terhadap Volume Penjualan Buah Desa Bulian - Sritini , Ni Komang Intan; Yulianthini, Ni Nyoman (Universitas Pendidikan Ganesha, 2023)
This study aims to examine the effect of product quality and social media marketing on sales volume, both simultaneously and partially. The research design used in this study is causal quantitative. The subjects in this study were people in Singaraja City aged 17-45 years, who had bought or consumed fruit products from Bulian Village. The object of this research is product quality, social media marketing and sales volume. Determination of the sample in this study using a purposive sampling technique. The number of samples used were 97 respondents. The instrument used in data collection was a questionnaire and the data analysis technique used was multiple linear regression analysis. The results of this study are (1) product quality has a positive and significant effect on sales volume, (2) social media marketing has a positive and significant effect on sales volume, (3) product quality and social media marketing has a significant effect on sales volume of fruit farming products the village of Bulian.